Modelling the household-level impact of a maternal respiratory syncytial virus (RSV) vaccine in a high-income setting - Campbell,P; Geard,N; Hogan,A (BMC Medicine, 2020)
Background: Respiratory syncytial virus (RSV) infects almost all children by the age of two years, with the risk of hospitalisation highest in the first six months of life. Development and licensure of a vaccine to prevent severe RSV illness in infants is a public health priority. A recent phase 3 clinical trial estimated efficacy of maternal vaccination at 39% over the first 90 days of life. Households play a key role in RSV transmission, however few estimates of population-level RSV vaccine impact account for household structure.Methods: We simulated RSV transmission within a stochastic, individual-based model framework, using an existing demographic model, structured by age and household and parameterised with Australian data, as an exemplar of a high-income country. We modelled vaccination by immunising pregnant women and explicitly linked the immune status of each mother-infant pair. We quantified the impact on children for a range of vaccine properties and uptake levels.Results: We found that a maternal immunisation strategy would have the most substantial impact in infants younger than 3 months, reducing RSV infection incidence in this age group by 16.6% at 70% vaccination coverage. In children aged 3–6 months, RSV infection was reduced by 5.3%. Over the first six months of life, the incidence rate for infants born to unvaccinated mothers was 1.26 times that of infants born to vaccinated mothers. The impact in older age groups was more modest, with evidence of infections being delayed to the second year of life.Conclusions: Our findings show that while individual benefit from maternal RSV vaccination could be substantial, population-level reductions may be more modest. Vaccination impact was sensitive to the extent that vaccination prevented infection, highlighting the need for more vaccine trial data.